COVID-19 and older adults: Representations from the Chilean Health Ministry - Salazar Norambuena, Carola (2021)
Social representations are a set of ideas, practices and ideals that are part of the common sense of a group. Generally, the study of older adults’representations is conducted by looking at the media, however, this research incorporates a key agent in the health/ disease /care processes: the Ministry of Health. The main objective of this article is to identify older adults’ representations found in the Chilean Ministry of Health (MINSAL) news portal website during the COVID-19 pandemic in 2020. Using framing analysis, four types of frames were found: age sub-groups, terms for referring to older adults, risk group and social solidarity. These four framesshare some ageist qualities, that is, they have a biased view of older people, representing them as a homogeneous, dependent and without agency group, since other people speak for them.